A Japanese man with community-onset carbapenem-resistant Stutzerimonas nitrititolerans bacteremia and a sacral pressure ulcer: a case report - Kohei Hasegawa; Kenya Murata; Yuki Suzuki; Yoshihiko Ogawa; Hisakazu Yano (BMC Infectious Diseases)
Abstract Background Stutzerimonas is a recently proposed genus comprising strains formerly classified as Pseudomonas stutzeri. The genus includes at least 16 identified species. Stutzerimonas nitrititolerans, previously known as Pseudomonas nitrititolerans, was initially isolated from a bioreactor. Only one case of human infection has been reported to date, and its pathogenicity remains unknown. Case presentation We present a case of community-acquired S. nitrititolerans bacteremia in a 77-year-old Japanese man with a sacral pressure ulcer. On admission for cerebral infarction, empirical ampicillin/sulbactam was administered because of an infected sacral pressure ulcer. Blood cultures revealed Gram-negative bacilli. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry was unable to identify the species, but 16 S ribosomal RNA gene sequencing identified the isolate NR5426 as S. nitrititolerans. Despite negative results for common carbapenem-resistance genes, the strain showed possible metallo-beta-lactamase production. The patient was treated with piperacillin/tazobactam and recovered. Conclusions This case confirms that S. nitrititolerans can cause infection in humans and highlights the antimicrobial susceptibility profile and the treatment strategy for infections caused by this rare bacterium. Further studies are required to determine its resistance mechanisms and the clinical implications.